COVID-19 reduces immune competence and precipitates superinfections - Josef Finsterer; Fulvio A. Scorza (Journal of Family Medicine and Primary Care, 2024)
Objectives: Whether infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can be complicated by immune suppression is under debate, but the following case suggests decreased immune competence during and after a SARS-CoV-2 infection. Case Report: The patient is a 50-year-old woman with a previous history of transient hyperthyroidism, allergy against ambrosia, and burn-out syndrome, who experienced a mild infection with SARS-CoV-2 during which she developed candida pharyngitis, which was successfully treated with miconazole. Twenty-eight days after clinical recovery from the SARS-CoV-2 infection, she developed right-sided zoster oticus with vestibular neuronitis and was successfully treated with acyclovir. Conclusions: The case suggests that infection with SARS-CoV-2 can weaken immune competence and precipitate the development of candidiasis and focal infection with the zoster virus. Even mild infections with SARS-CoV-2 may be complicated by immune-compromise and immune-concomitant superinfections, which is why coronavirus disease 2019 (COVID-19) patients should strengthen their immune system not only during but also after the infection.